Islam: history, religion, and politics - Sonn, Tamara (Wiley Blackwell brief histories of religion series, 2016)
"Now available in a fully revised and updated third edition, Islam: History, Religion and Politics, provides a comprehensive and engaging introduction to the core teachings, historical development, and contemporary public struggles of Islam. Featuring a new chapter on the Arab Spring, this edition also includes up-to-date analysis of the civil wars in Afghanistan, Syria, Iraq, and Yemen, and a detailed study of the rise of modern terrorist groups Boko Haram and ISIS. This illuminating introduction spans Islamic history from the life of Muhammad and the birth of Islamic ideals, through Islam's phenomenal geographical expansion and cultural development, to the creation of modern states and Islam's role in today's global society. Written by a leading scholar of Islamic studies, the third edition of this well-respected introduction will continue to be an essential tool for anyone interested in better understanding the evolution of this influential and politically-charged world religion"--